Emotions as Categories : Analysing Jeremy Pober’s Critique for the Theory of Constructed Emotion - Lindström, Elina (My University, 2025)
This thesis discusses the Theory of Constructed Emotion and Jeremy Pober's 2018 critique of it. The theory presents a neuroscientific explanation for how emotions are created in the brain through a categorization process. It argues that emotions are multimodal situational constructs and have no singular identifiable biological basis; they are abstract conceptual categories. The theory combines the latest advancements in neuroscience with social constructivism, offering both a mechanistic neurophysiological explanation for the creation of emotions and a theory for emotions ontology. It argues emotions are social objects, drawing a theory for emotions ontology primarily from John Searle’s (1995) theory for social objects. I reflect on this and present a possible alternative framework for conceptualizing emotions as events rather than social objects. This thesis focuses on emotions as categories and analyses Jeremy Pober’s critique for the implications of the categorization process. Pober argues that emotions are constitutively internal and cannot therefore be considered social objects. He also argues that the categorization process for emotions results in seemings of being in an emotional state, not actual emotions. I argue that the arguments ignore or misinterpret parts of The Theory of Constructed Emotion and can therefore be countered by a more precise and consistent definition of the categorization process the theory presents, as well as what the theory claims emotions to be.
Keywords: Theory of Constructed Emotion, emotions as categories, philosophical psychology, emotion ontology, neuroscience, neurophilosophy